Employment Insertion of Graduates of Commercial Engineering / Business Administration of Category A and B Universities of the Province of Pichincha – Ecuador - Pineda-López, Rosario del Carmen (2021)
The purpose of the research is to identify the factors that affect the labor insertion of graduates of the career of Commercial Engineering / Business Administration of the Universities category “A and B” of the Province of Pichincha Ecuador.  Methodologically, the current situation of the insertion of graduates will be analyzed, the limitations that they have encountered for their labor insertion, the personnel selection policies of the companies to determine the profiles and skills required, and finally, the opinion of the Directors. of the careers on the actions that the universities undertake to facilitate the insertion of their graduates. The present study is conceived from the mixed approach of the investigation, of descriptive type with non-experimental field design. Among the main results, the development of The main competencies on which the effort should focus are: ability to solve problems, Teamwork, Leadership, and Decision-making. In addition, it should be considered that instrumental mastery of the English language. For the development of the main competences, specific activities will be necessary aimed at solving specific situations through the analysis of business cases or the presentation and evaluation of real projects.